Site-specific Phosphorylation of Histone H3K36 Methyltransferase Set2p and Demethylase Jhd1p is Required for Stress Responses in Saccharomyces cerevisiae. Issue 7 (15th April 2022) - Separovich, Ryan J.; Wong, Mandy W.M.; Bartolec, Tara K.; Hamey, Joshua J.; Wilkins, Marc R.
Graphical abstract: Highlights: The functions of phosphosites on histone methylation enzymes are poorly understood. 82 phosphosite mutants were generated and screened for changes in histone methylation. An N-terminal phosphorylation cluster on Set2p regulates the diamide stress response. Serine 44 phosphorylation of Jhd1p is associated with the cold stress response. Phosphorylation of histone methylation enzymes is essential for responses to stress. Abstract: Histone lysine methylation is a key epigenetic modification that regulates eukaryotic transcription. In Saccharomyces cerevisiae, it is controlled by a reduced but evolutionarily conserved suite of methyltransferase (Set1p, Set2p, Dot1p, and Set5p) and demethylase (Jhd1p, Jhd2p, Rph1p, and Gis1p) enzymes. Many of these enzymes are extensively phosphorylated in vivo; however, the functions of almost all phosphosites remain unknown. Here, we comprehensively analyse the phosphoregulation of the yeast histone methylation network by functionally investigating 40 phosphosites on six enzymes. A total of 82 genomically-edited S. cerevisiae strains were generated through mutagenesis of sites to aspartate as a phosphomimetic or alanine as a phosphonull. These phosphosite mutants were screened for changes in native H3K4, H3K36, and H3K79 methylation levels, and for sensitivity to environmental stress conditions. For methyltransferase Set2p, we found that phosphorylation at threonine 127 significantly decreased H3K36 methylation in vivo, and that an N-terminal phosphorylation cluster at serine residues 6, 8, and 10 is required for the diamide stress response. Proteomic analysis of Set2p phosphosite mutants revealed a specific downregulation of membrane-associated proteins and processes, consistent with changes brought about by SET2 deletion and the sensitivity of mutants to diamide. For demethylase Jhd1p, we found that its sole phosphorylation site at serine 44 is required for the cold stress response. This study represents the first systematic investigation into the phosphoregulation of the epigenetic network in any eukaryote, and shows that phosphosites on histone methylation enzymes are required for a normal cellular response to stress in S. cerevisiae.